Atmosphere‐Controlled Chemoselectivity: Rhodium‐Catalyzed Alkylation and Olefination of Alkylnitriles with Alcohols. Issue 58 (25th September 2017) - Li, Junjun; Liu, Yuxuan; Tang, Weijun; Xue, Dong; Li, Chaoqun; Xiao, Jianliang; Wang, Chao
Abstract: The chemoselective alkylation and olefination of alkylnitriles with alcohols have been developed by simply controlling the reaction atmosphere. A binuclear rhodium complex catalyzes the alkylation reaction under argon through a hydrogen‐borrowing pathway and the olefination reaction under oxygen through aerobic dehydrogenation. Broad substrate scope is demonstrated, permitting the synthesis of some important organic building blocks. Mechanistic studies suggest that the alkylation product may be formed through conjugate reduction of an alkene intermediate by a rhodium hydride, whereas the formation of olefin product may be due to the oxidation of the rhodium hydride complex with molecular oxygen. Abstract : There's something in the air : A binuclear rhodium complex catalyzes the chemoselective alkylation and olefination of alkylnitriles with alcohols, with the selectivity controlled solely by the reaction atmosphere. The reactions have broad substrate scope and could be applied to the synthesis of unique amino acids.